Dengue Fever in a One Health Perspective Latest Research and Recent Advances - Aparecida Sperança, Márcia (Infectious Diseases, 2023)
Dengue Fever in a One Health Perspective - Latest Research and Recent Advances presents studies on dengue fever (DF) and dengue virus (DENV) that discuss eco-epidemiology, physiopathology, and new biotechnological tools to fight against this important disease in the context of the World Health Organization's One Health strategy. The book is organized into five sections: "Epidemiological Aspects", "Environmental Aspects", "Pathogenicity", "Diagnosis and Treatment" and "Management Strategies". The chapters address topics such as DF prevalence and management in a Chinese county, the risk of DF in American children younger than 15 years, the silent transmission of DENV by asymptomatic individuals, the use of X-ray and ultrasound to identify severe DF cases, gene-silencing techniques to investigate biological aspects of DF, viral genomic surveillance to promote early intervention in DF epidemics, and much more.